A Comparative Exploration of Quality Assurance Results by the Third-Party Pharmaceutical Education Evaluation in Japan - Kayoko Takeda; Naoko Arakawa (MDPI AG, 2020)
Background: The Standards for the Establishment of Universities in Japan were revised; subsequently, the number of schools or universities of pharmacy/pharmaceutical sciences increased from 46 in 2002 to 74 in 2016.The pharmacy education programme was also changed from four to six years, which was implemented in 2006. In this study, we provide the comparative results of the first cycle of the third-party accrediting organization, the Japan Accreditation Board for Pharmaceutical Education (JABPE); Methods: The results of the first cycle of all universities or schools of pharmacy assessed by the JABPE from JABPE website were retrieved, and we collated and compared the results based on the 13 areas of the assessment standards; Results: In "improvements", the number of public universities or schools was less than that of private universities or schools, and the number of old private universities or schools was also less than the number of new private universities or schools in all assessment areas. Conclusions: These results suggest that new universities or schools established since 2003 have not yet established their own quality assurance mechanism within the institutions. We need to review the Japanese pharmacy education system or the assessment criteria for it to bring about essential change.